Computer guided maxillo-malar piezoelectric osteotomies for midface augmentation. (January 2023) - Lazzarotto, Andrea; Tel, Alessandro; Brontoladi, Serena; Sembronio, Salvatore; Costa, Fabio; Robiony, Massimo
Summary: Purpose: Despite maxillo-malar osteotomies having been discarded in the most recent literature, in the setting of orthognathic surgery they provide several advantages for middle third augmentation. This paper reintroduces maxillo-malar osteotomies as an effective method to increase volume of midfacial region in combination with contemporary technology, including piezosurgery, virtual surgical planning, and navigation. Material and Methods: Eighteen patients with midface hypoplasia were included in this study and underwent orthognathic surgery with maxillo-malar osteotomies. All patients underwent the same workflow: virtual design of maxillo-malar osteotomies, surgery with navigation-assisted piezoelectric osteotomies, and computerized morphometric analysis. Results: Simulated maxillo-malar osteotomies were successfully replicated in the operating room, as shown by accuracy evaluation performed using three-dimensional analysis. In long-term follow-up period, no permanent complications were assessed. Superimposition between postoperative and preoperative CBCTs revealed that the soft tissue area influenced by the underlying skeletal movement was comparable for all cases. Conclusions: Virtual surgical planning, navigation, and piezosurgery are today indispensable tools to perform maxillo-malar osteotomies safely and accurately. We suggest incorporating such osteotomies in the surgeon's armamentarium for patients with severe midfacial hypoplasia as they offer an integrated solution to restore functionality and aesthetics.